THE EFFECT OF PRACTICING DHUHA PRAYER IN CONGREGATION ON IMPROVING STUDENT CONCENTRATION AND SPIRITUAL INTELLIGENCE AT DHARMA ASIH SPECIAL EDUCATION SCHOOL IN KRAKSAAN - Raini Rosdiana Wasila, Alisyah; Khumaidi, Ahmad; Purwantoro, Farich (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2026)
This study aims to analyze the effect of cultivating the habit of performing Dhuha prayer in congregation on improving students concentration in learning and spiritual intelligence at the Dharma Asih Special Education School (SLB) in Kraksaan. The background of this study is based on the limited number of empirical studies that specifically examine religious habit-forming programs in special education settings (SLB). The study employed a quantitative, associative design involving 65 students selected through purposive sampling from a total population of 78 students ranging from elementary to high school levels. Data were collected using questionnaires for the variables of Dhuha prayer practice and spiritual intelligence, as well as performance-based tests for academic concentration. Data analysis included descriptive statistics, tests of normality and homogeneity, and hypothesis testing using the t-test. The results showed that the practice of congregational Dhuha prayer had a significant effect on learning concentration (calculated t = 4.87 > table t = 1.998, sig. = 0.000) with a contribution of 38.6%, and has a significant effect on students spiritual intelligence (t-calculated = 5.23 > t-table = 1.998, sig. = 0.000) with a contribution of 42.4%. These findings confirm that structured religious practices in the special education school environment can positively support the cognitive and spiritual development of students with special needs.